Save the planet 2.0: A mini review of improving agricultural soil with terra preta - Norazlianie, Sazali; Kettner, Maurice; Salim, Naqib (Semarak Ilmu Publishing, 2025)
As climate change intensify and environmental degradation occurs, the urgency for sustainable farming techniques becomes important. Terra Preta has been known as an ancient soil amendment, that has remarkable capabilities to improve soil fertility and carbon sequestration. This review offers in-depth assessment of Terra Preta by tracing its historical origins, inspecting its production processes, and exploring its contemporary utilization. By synthesizing findings from a wide array of scientific studies and field applications, this paper clarifies the deep potential of Terra Preta in increasing yield of crops, enhancing soil health and mitigating significantly to climate change. Moreover, it addresses the obstacles and proposes ways forward for successfully incorporating Terra Preta into modern farming techniques, which highlighting its role in promoting a resilient and sustainable agricultural paradigm.